PENGEMBANGAN MODIFIKASI PERMAINAN BOLA BASSHOLL DALAM PEMBELAJARAN BOLA BESAR PENJASORKES BAGI KELAS V SEKOLAH DASAR NEGERI DELIK 02 KEC. TUNTANG KAB. SEMARANG TAHUN AJARAN 2012/2013 (Department of Physical Education, Sport, Health and Recreation, 2014)
This research method is the study of expansion. As for product development procedures include analysis of products will be developed, developing the initial product, and revision of validation, testing and revision of the small group, large group trials and the final product. Data collection was done using field observations and questionnaires obtained from the evaluation and the results of the questionnaire by the students filling. Data analysis technique used is descriptive percentage. From the experimental results obtained percentage of the average yield analysis products 86% with good size. Therefore it can be used for a small group of trial. Data from the questionnaires students in small group trials the average response obtained with the percentage of 83.07% with good category. And student outcome data questionnaires trials large group obtained the answers to the percentage of 87.23% with good category. Students have not found any difficulties and fear again when playing bassholl.